Protection for the Rights and Interests of Local Communities Adversely Affected by Multinational Energy Companies’ Activities - Purwaningsih, Putu (Udayana Journal of Law and Culture; Vol 6 No 1 (2022)DO - 10.24843/UJLC.2022.v06.i01.p01, 2022)
Foreign investments of Multinational Corporations (MNCs) bring several advantages for the host states where they operate. In the case of foreign investment in the energy sector, the business activities of MNCs have an impact on social and environmental issues that adversely affect the right and interests of the local communities. In terms of addressing such problems, some binding and non-binding international legal instruments were established and adopted by states and international organizations/bodies. This article discusses the sufficiency of the protection provided by international law for the local communities adversely affected by MNCs in the energy sector especially with regards to human rights, environmental, and anti-corruption matters. This article argues that protection of the rights and interests of local communities from the activities of MNCs are developed through an international legal framework, both general and bilateral treaties, as well as the national law of host States.